Determination of Mount Eruption Insurance Premiums in Indonesia Based on Collective Risk and Level of Risk Spread - Kalfin, Kalfin; Sukono, Sukono; Januaviani, Trisha Magdalena Adelheid; Siregar, Bakti (International Journal of Business, Economics, and Social Development, 2024)
Volcano eruption insurance is an insurance product that provides financial protection to policy holders who experience losses due to volcanic eruptions. This insurance product is still rarely developed in Indonesia, even though this country is very vulnerable to natural disasters. Therefore, this research aims to carry out a simulation of determining volcanic eruption disaster insurance premiums based on collective risk and the level of risk distribution. The data used in this research is the frequency of events and economic losses due to volcanic eruptions. Event frequency and loss data are analyzed using a collective risk model. Apart from that, determining insurance premiums also takes into account loading factors and the level of risk distribution from volcanic eruption disaster data. From the results of the analysis, it was found that natural disaster insurance premiums had increased, along with an increase in the loading factor provided. In addition, insurance premium expenses are influenced by the collective risks faced by customers. The greater the collective risk faced, the greater the insurance premium that customers must bear. Based on the results of the estimates carried out, it is hoped that this research can provide an overview to the Indonesian government in estimating the Mount Meletus insurance scheme. Meanwhile, insurance companies can get an idea of determining insurance premiums according to conditions in the field.